EXPERIMENTAL STUDY OF IOT SENSOR PERFORMANCE FOR BUILDING MOVEMENT MONITORING - Sari, Sely Novita; Pratama, Bagus Gilang; Prasojo, Joko (KURVATEK, 2025)
Real-time monitoring of building movement is essential to mitigate structural damage risks, particularly in earthquake-prone regions. The application of Internet of Things (IoT) technology enables continuous and efficient measurement of structural deformation and inclination through the integration of smart sensors and cloud-based systems. The primary objective of this study is to evaluate the performance of a MEMS-based IoT sensor system in detecting displacement and angular changes in building structures. An experimental laboratory test was conducted by comparing the readings of accelerometer, gyroscope, and inclinometer sensors with standard measuring instruments. Results indicate an average measurement error of 1.58%, a response time of 2.34 seconds, and data transmission reliability of 97.8%, demonstrating high accuracy and stability. The integration of sensors, an ESP32 microcontroller, and a cloud computing platform shows strong potential for implementation as an effective IoT-based Structural Health Monitoring (SHM) system, supporting the development of resilient and sustainable smart infrastructure